Experimental study of axially compressed cold formed steel channel columns - Kalavagunta S.; Naganathan S.; Mustapha K.N.B. (2023)
Analysis and design of axially compressed cold formed steel channel section presented in this paper was conducted through experimental study, design based on British standards and North American Specification for the design of cold-formed steel structural members. More than 18 laboratory experiments were undertaken first on these steel channel columns under axial compression. A series of parametric studies were also carried out by varying the thickness and column length. All of these columns failed by local and distortional buckling. The test results were compared with American (AISI-2007) and British Standards (BS5950-Part5) for the design of cold-formed steel structural members. The details of these investigation and the outcomes are presented in this paper.